2009
DOI: 10.1364/ao.48.00h120
|View full text |Cite
|
Sign up to set email alerts
|

Review of three-dimensional holographic imaging by multiple-viewpoint-projection based methods

Abstract: Methods of generating multiple viewpoint projection holograms of three-dimensional (3-D) realistic objects illuminated by incoherent white light are reviewed in this paper. Using these methods, it is possible to obtain holograms with a simple digital camera, operating in regular light conditions. Thus, most disadvantages characterizing conventional digital holography, namely the need for a powerful, highly coherent laser and extreme stability of the optical system, are avoided. The proposed holographic process… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(52 citation statements)
references
References 65 publications
(117 reference statements)
0
52
0
Order By: Relevance
“…During II recording, an elemental image array is generated, that has different views of the object. One advantage of II is that only a single exposure is required to obtain 3D information; no calibration is needed, unlike stereo imaging, and no active illumination is needed, unlike holography or light detection and ranging (LIDAR) [12,13]. A depth extraction technique using elemental images has been studied in [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…During II recording, an elemental image array is generated, that has different views of the object. One advantage of II is that only a single exposure is required to obtain 3D information; no calibration is needed, unlike stereo imaging, and no active illumination is needed, unlike holography or light detection and ranging (LIDAR) [12,13]. A depth extraction technique using elemental images has been studied in [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Holographic stereogram synthesis using sequential images from multiple camera viewpoints was first demonstrated using incoherent scene illumination by McCrickerd et al in 1968 8 and has since developed into a mature technique. In particular, several studies 9 have examined digital techniques for assembling multiple incoherently-imaged viewpoints of a scene into digital or optical holograms. Recently, Blanche et al demonstrated holographic telepresence 10 using a re-writable photorefractive material; holographic images were written to the material after the post-processing of sixteen viewpoint images of a scene.…”
Section: Related Work and Motivationmentioning
confidence: 99%
“…The II recording process generates a set of elemental images with an array of pinholes or microlenses, thus an elemental image has different perspectives of a 3D object. Unlike stereo imaging, multiple-perspective imaging of an object can yield a compact 3D sensing system, as only a single exposure is required without any active illumination, unlike holography or light detection and ranging [15][16][17].…”
Section: Introductionmentioning
confidence: 99%